Genetic chronicles: Stories written in ancient DNA - Wiktoria Wisniewska (BioScientist: The Salford Biomedicine Society Magazine, 2024)
This article focuses on the way ancient DNA research has reshaped our understanding of human history, as well as explore the ethical concerns surrounding aDNA research. As scientists uncover genetic information from long-extinct populations, ethical dilemmas related to consent, cultural sensitivity, and the potential for misuse of genetic data arise. This piece sheds light on the balance between scientific advancement and respect for the communities connected to these ancient remains, as well as address the responsibilities researchers have toward descendant communities to guide ethical aDNA research. This article has been reviewed by Assoc. Prof. Robin Beck, Reader in Biology, University of Salford. The Editorial Team would like to thank him for his time and contributions.